Anemia Defisiensi Besi Berat pada Remaja - As Siddiqi, Abdurrahman Arsyad; Izzah, Amirah Zatil (Majalah Kedokteran Andalas, 2024)
Iron deficiency anemia (IDA) is anemia caused by a reduced body iron reserve to form red blood cells. During periods of rapid growth, such as the first year of life and adolescence, the need for iron increases, leading to an increased incidence of iron deficiency anemia during these periods. Deficiency of iron can lead to concealed intestinal bleeding. This case report discusses a 10-year and 7-month-old male patient with a diagnosis of severe iron deficiency anemia accompanied by occult bleeding. The patient received a blood transfusion due to a very low Hb level of 3.9 g/dl. The transfusion was administered gradually with a target Hb of 6 g/dl and was followed by iron supplementation. The blood transfusion provided was in the form of red cell packs, administered slowly in sufficient amounts to raise the Hb to a safe level.